Intestinal Gastrin/CCKBR (Cholecystokinin B Receptor) Ameliorates Salt-Sensitive Hypertension by Inhibiting Intestinal Na+/H+ Exchanger 3 Activity Through a PKC (Protein Kinase C)-Mediated NHERF1 and NHERF2 Pathway. Issue 8 (8th June 2022) - Jiang, Xiaoliang; Liu, Yunpeng; Zhang, Xin-Yang; Liu, Xue; Liu, Xing; Wu, Xianxian; Jose, Pedro A.; Duan, Shun; Xu, Fu-Jian; Yang, Zhiwei
Abstract : Background: The present study directly tested the crucial role of intestinal gastrin/CCKBR (cholecystokinin B receptor) in the treatment of salt-sensitive hypertension. Methods: Adult intestine-specific Cckbr -knockout mice ( Cckbr fl/fl villin-Cre ) and Dahl salt-sensitive rats were studied on the effect of high salt intake (8% NaCl, 6–7 weeks) on intestinal Na +/ H + exchanger 3 expression, urine sodium concentration, and blood pressure. High-salt diet increased urine sodium concentration and systolic blood pressure to a greater extent in Cckbr fl/fl villin-Cre mice and Dahl salt-sensitive rats than their respective controls, Cckbr fl/fl villin mice and SS13 BN rats. We constructed gastrin-SiO2 microspheres to enable gastrin to stimulate specifically and selectively intestinal CCKBR without its absorption into the circulation. Results: Gastrin-SiO2 microspheres treatment prevented the high salt-induced hypertension and increase in urine Na concentration by inhibiting intestinal Na +/ H + exchanger 3 trafficking and activity, increasing stool sodium without inducing diarrhea. Gastrin-mediated inhibition of intestinal Na +/ H + exchanger 3 activity, related to a PKC (protein kinase C)-mediated activation of NHERF1 and NHERF2. Conclusions: These results support a crucial role of intestinal gastrin/CCKBR in decreasing intestinal sodium absorption and keeping the blood pressure in the normal range. The gastrointestinal administration of gastrin-SiO2 microspheres is a promising and safe strategy to treat salt-sensitive hypertension without side effects.